Multiplexed immunoassay for a serum autoantibody biomarker panel in diagnostic and prognostic prediction of canine mammary tumors - Wu, Chih-Ching; Chang, Chia-Yu; Chou, Pei-Yi; Chan, Xiu-Ya; Huang, Chun-Chueh; Yang, Youngsen; Liu, Hao-Ping (The Veterinary quarterly, 2025)
Canine mammary tumor (CMT) is a prevalent and destructive disease often diagnosed at an advanced stage, leading to poor outcomes. Currently, there is a lack of effective biomarkers for early detection and prognostic prediction of CMT. To improve CMT detection, we established a multiplexed immunoassay using a fluorescence bead-based suspension array system to measure serum levels of autoantibodies against four CMT-associated proteins (AGR2, HAPLN1, IGFBP5, and TYMS) in CMT patients. Our data revealed that serum levels of the four autoantibodies (anti-AGR2, anti-HAPLN1, anti-IGFBP5, and anti-TYMS) were significantly elevated in CMT patients ( = 158) compared to healthy individuals ( = 39). Notably, serum levels of anti-AGR2, anti-HAPLN1, and anti-TYMS in the dogs with stage I CMT ( = 56) were higher than those in the healthy group. Using a marker panel consisting of the four autoantibodies for detecting malignant CMT ( = 125) achieved a sensitivity of 50.4% and a specificity of 90%. Furthermore, higher levels of anti-AGR2, anti-HAPLN1, anti-IGFBP5, and anti-TYMS were associated with poorer survival in CMT patients. Collectively, we established a multiplexed immunoassay platform to detect serum autoantibodies and demonstrated that a tailored autoantibody marker panel shows potential clinical applicability for the diagnosis and prognosis of CMT.